Cryptanalysis of PASS II and MiniPass - Goi, , BM; Siddiqi,, MU; Ding, , JT (2005)
In ACISP '00, Wu et al. proposed attacks to break the Polynomial Authentication and Signature Scheme (PASS), in particular, they are able to generate valid authentication transcripts and digital signatures without knowing the private key and any previous transcripts/signatures. They showed that PASS can be broken with around 2(38.3) trials. In this paper, we analyze the security of the improved versions of PASS; viz. PASS II and MiniPASS, and extend the Wu et al.'s attacks to PASS II and MiniPASS to break them. Furthermore, we discuss why and how these schemes are broken from the view point of the structure of cryptosystems and point out the fundamental weakness behind.